Trends in the Incidence and DALYs of Urolithiasis From 1990 to 2019: Results From the Global Burden of Disease Study 2019 - Li, Shasha; Huang, Xueying; Liu, Jie; Yue, Suru; Hou, Xuefei; Hu, Liren; Wu, Jiayuan (Frontiers in Public Health, 2022)
Objectives To provide a comprehensive assessment of the estimated burden and trend of urolithiasis at the global, regional, and national levels. Methods The age-standardized rates (ASRs) of the incidence and disability-adjusted life years (DALYs) of urolithiasis from 1990 to 2019 were obtained from the Global Burden of Disease Study 2019 database. Estimated annual percentage changes (EAPCs) were calculated to quantify the temporal trends in urolithiasis burden. Results In 2019, the ASRs of the incidence and DALYs were 1394.03/100 000 and 7.35/100 000, respectively. The ASRs of the incidence and DALYs of urolithiasis decreased from 1990 to 2019 with EAPCs of −0.83 and −1.77, respectively. Males had a higher burden of urolithiasis than females. In 2019, the highest burden of urolithiasis was observed in regions with high–middle sociodemographic index (SDI), particularly in Eastern Europe, Central Asia, and Southeast Asia. The burden of urolithiasis increased in most countries or territories. The burden of urolithiasis and SDI had a non-linear relationship, and the estimated value of urolithiasis burden was the highest when the SDI value was approximately 0.7. Conclusion Globally, the ASRs of the incidence and DALYs of urolithiasis decreased from 1990 to 2019, but an increasing trend was observed among many countries. More effective and appropriate medical and health policies are needed to prevent and early intervene in urolithiasis.